Relações de trabalho dos operários da Faville de Marechal Cândido Rondon/PR - Tebaldi, Enegelly Antonia Pilar (2009)
This thesis investigates the workplace relations at Faville, a factory located in the West Paraná State (Marechal Cândido Rondon city), during the years 1990 to 2008, when industrial park has constituted in the city. The main point is about the understanding of workplace relations these "new" workers within a national context marked by processes called "restructuring process". The Faville started operations it in late 1990, when the majority of studies have emphasized the work changes and transformations, it including organizations and working methods. From the analysis of the sources produced by the company, it was possible to identify many strategies developed to try to promote specific consent on sphere of production among workers. However, from the discussion about experiences their, that attempt to consent is not performed. In the fact, the various mechanisms used to convince the workers about Faville goals have been coercive practices that force their employees to follow the politics of production by the company. Reinforcing this manufacturing system is a strong felling of fear, fear of to lose their jobs, felling that is lived for most workers. Finally, it has done many bad consequences on labor rights, mainly on the initiatives to organize unions at that factory.